Pesan Pertobatan dalam Yunus 3:1-10: Analisis Tafsir Tentang Belas Kasih Allah Bagi Bangsa-Bangsa - Yosef Noel; Whisye Kasih Kesysia; Eliana Kiding Allo; Dinda Rapa Langi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This study aims to examine the message of repentance in Jonah 3:1-10 through an interpretive analysis focusing on the manifestation of God's mercy toward non-Israelite nations. The background of this study is rooted in the theological tension between Israel's exclusivism and the universality of God's love reaching Nineveh, a nation notorious for its cruelty. The method used is qualitative with a historical-grammatical exegesis approach to uncover the meaning of the text in its original context. The research results show that Nineveh's repentance was a radical response to the warning of judgment, involving all elements of society from the common people to political authorities. This phenomenon proves that the primary purpose of God's prophecy of judgment is not destruction, but the transformation of human behavior. This analysis confirms that God's mercy is sovereign and transcends ethnic or geographical boundaries. The implications of this research emphasize the importance for modern faith communities to adopt an inclusive attitude and understand that the sovereignty of God's love cannot be limited by human prejudice against groups perceived as strangers or enemies